IMPACTS ON VEGETATION AFTER SELECTIVE CUTTING IN FOREST CONCESSION AREA IN THE SOUTHWESTERN BRAZILIAN AMAZON - Felberg Jacobsen, Raquel Helena; Volpato Sccoti, Marta Silvana; Fagundes, Suelen Thaina Silva; Brito Junior, João Fideles de; Biazatti, Scheila Cristina (Floresta, 2020)
The forest monitoring after exploration activities is an important tool for forest management, helping to plan the use of forest resources. This research aimed to evaluate the impacts on tree vegetation after one year of the end of forest harvesting in concession area in the Jamari National Forest, RO. The vegetation was evaluated before and after the exploitation in an Annual Production Unit (APU) with cutting rate of 14.14 m³ ha-1. In total, seven permanent plots of 0.5 ha were divided and randomly distributed, where all individuals with diameter at breast height (DBH) ≥ 10 cm were evaluated. Impact evaluation was based on two criteria, the diversity and structure of vegetation (phytosociological, parametric, diametric, and internal). There was a reduction of 2% in plant density and loss of two species. The volumetric supply decreased in the classes above 80 cm of DBH and the diametric structure maintained the largest supply of plants in the lower classes. The exploration activities collaborated in 3.57% to increase the mortality rate, besides causing slight and severe damages in 15 ind.ha-1. The quality of the stem was predominantly straight (82.36%). The damage observed is within the expected limits for areas with low cut rates and subjected to reduced impact exploration techniques. We suggest the continuous monitoring in the medium- and long- term in order to describe the patterns of regeneration and growth of species, mainly logging, projecting the future supply of cutting. Keywords: Management in natural forests; Forest dynamics; Forest concession.